Från klass till klass - frågor runt klassamhällets återkomst: Perspektiv på klassamhällets former - Bodén, Daniel (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2023)
This is an introduction to a thematic issue on the concept of class, in celebration of Professor Mats Lindqvist, who unfailingly and successfully has argued the relevance of including the social organisation of economic practice and class into Swedish ethnology. In the text, two basic tenets of general class theory are laid out. One drawing from the “historical materialist” and “dialectical”, Marxist tradition, and the other from a more “scalar” and “situational”, “Weberian” canon. These are then used as analytical tools to understand the development of class studies within the discipline of ethnology. While illustrating how Swedish ethnological studies, with their preoccupation with the situational social construction of meaning has come to prioritise the “scalar” before the “dialectical”, the author thus provokingly argues that any substantial critique of the current socio-economical formation that might have existed within the discipline before, has seemingly diminished.